Correlations between Waist and Neck Circumferences and Obstructive Sleep Apnea Characteristics - Tom, Chloe (Sleep Vigil, 2018)
PURPOSE: The body mass index (BMI), an estimate of body fat, provides a rather imprecise indication of risk for obstructive sleep apnea (OSA). We examined whether other measures, including waist and neck circumference, provide improved indicators of risk in treatment-naïve OSA subjects. METHODS: We studied 59 OSA subjects [age, 48.8±10.0 years; BMI, 31.9±6.6 kg/m(2); apnea-hypopnea-index (AHI), 38.5±23.0 events/hour; sleep efficiency index (SEI, n=52), 78.6±14.4%; lowest oxygen saturation (SaO(2) nadir), 79.5±8.0%; systolic blood pressure (BP), 127.4±15.7 mmHg; diastolic BP, 80.1±9.1 mmHg; 43 male), and determined waist and neck circumferences (waist, 107.4±15.3 cm; neck, 41.8±4.7 cm), daytime sleepiness [Epworth sleepiness scale (ESS), 8.7±4.6], sleep quality [Pittsburgh sleep quality index (PSQI), 8.5±4.1], depression levels [Beck depression inventory II (BDI-II), 6.6±5.7), and anxiety levels [Beck anxiety inventory (BAI), 6.2±7.2]. We used partial correlation procedures (covariates, age and gender) to examine associations between BMI, waist, and neck circumferences vs. AHI, sleep, and neuropsychological variables. RESULTS: BMI, waist, and neck circumferences were significantly correlated with SaO(2) nadir (BMI; r=−0.423, p=0.001; waist; r=−0.457, p<0.001; neck; r=−0.263, p=0.048), AHI (BMI; r=0.349, p=0.008; waist; r=0.459, p<0.001; neck; r=0.276, p=0.038), and systolic BP (BMI; r=0.354, p=0.007; waist; r=0.321, p=0.015; neck; r=0.388, p=0.003). SEI was significantly correlated with waist circumference (r=0.28, p=0.049), but higher with BMI (r=0.291, p=0.04). CONCLUSIONS: No other significant waist or neck correlations emerged. This study suggests that waist and neck measures correlate better than BMI with select disease severity (SaO(2) nadir and AHI) in OSA subjects. The findings offer an easily-measured, ancillary means to assess OSA risk.